CULTURAL HEGEMONY AND MEDIA FRAMING: A CRITICAL DISCOURSE ANALYSIS OF POLITICAL NARRATIVES - Abdul Rahman (Public Studies and Business Administration Journal (PUSBA), 2025)
In the contemporary political landscape, mass media has evolved from a mere information channel into a strategic instrument for the production of cultural hegemony. This study aims to comprehensively review the discursive strategies used by the media to naturalize political narratives into collective "common sense" by integrating Antonio Gramsci's concepts with the Critical Discourse Analysis (CDA) framework. Employing a narrative-thematic synthesis approach of global literature from Scopus and Web of Science databases between 2016-2026, this study analyzes the dialectical relationship between media discourse, ideology, and power. The findings reveal that ideological naturalization is executed through micro-linguistic strategies such as nominalization and passive constructions that obscure political agency, as well as the use of euphemisms and metaphors to legitimize controversial policies. At a macro level, media ownership concentration and the dominance of digital algorithms reinforce the reproduction of hegemony by creating echo chambers that marginalize alternative voices. While social media provides space for counter-publics and counter-hegemonic discourse, its effectiveness remains constrained by the technological structures of global platforms. This research concludes that modern media hegemony operates through gradual and institutionalized consensus-building, necessitating a multidimensional approach that integrates discursive and material dimensions to understand global power dynamics.